The Study Of Making Paving Block Using Bottom Ash And Plastic Waste - Surya Hosea Imanuel (President University, 2022)
There is a lot of coal ash waste in Indonesia because most power plants in Indonesia still use coal. And Indonesia produces quite a lot of plastic waste because most people use plastic in their daily lives. Plastic waste and bottom ash can be used as raw materials in the manufacture of paving blocks. The objective of this study is to find out the quality of paving blocks, comply with SNI 03-0691-1996, and find out whether the composition of the bottom ash and plastic waste affects the compressive strength and water absorption. The paving blocks to be made are 10 cm X 10 cm X s10 cm with 5 (five) different types of composition, each composition will have 2 (two) paving blocks, and the drying time is 14 days. This final project uses experimental methods, and T-test, analysis of variance (ANOVA). T-test testing is carried out on each type of quality, namely the quality of A, B, C, and D. 5 different types of compositions produce different qualities, namely the average compressive strength of composition 1 to 5 in order are, 4.76 MPa, 11.56 MPa, 11.4 MPa, 7.65 Mpa and 10.13 MPa. And for water absorption the average water absorption in composition 1 to 5 in order are, 2.08%, 2.16%, 2.18%, 3.12%, and 4.14% . From the T-Test result, paving blocks with compositions 2,3, and 5 have D quality because their compressive strength has complied with D quality even though the water absorption has met A quality. It means paving with compositions 2,3, and 5 can be used as building materials for the garden. And paving blocks with compositions 1 and 4 have A quality, so people can be used as materials for roads. Based on the ANOVA result, the factors of plastic waste and bottom ash significantly influence the compressive strength and water absorption quality.